Global talent management and staffing in MNEs - Guo, Ying, 1967-; Rammal, Hussain G.; Dowling, Peter J. (Bingley, U.K. : Emerald, 2016)
Attracting, managing and retaining talented employees is an important area of human resource management. Managing talent across an organization's global network presents many challenges including expatriation and repatriation issues, cross-cultural adjustment of employees, and operating in different regulatory and economic environments. This volume provides insights into multinational enterprises' (MNEs) global staffing and global talent management (GTM), and covers issues of global mobility from organizational, individual and contextual perspectives. The chapters in this edited volume cover historical development of expatriation, use of self-initiated and company-assigned expatriates, talent management in entrepreneurial firms, and talent retention through effective expatriation and repatriation programs in transitioning and emerging economies.
Expatriate selection: a historical overview and criteria for decision-making / Dana Ott, Snejina Michailova -- Global talent management: international staffing policies and practices of South Korean multinationals in China / Haiying Kang, Jie Shen -- How do assigned and self-initiated expatriate CEOs differ? an empirical investigation on CEO demography, personality, and performance in China / Charlotte Jonasson, Jan Selmer, Jakob Lauring, Ling Eleanor Zhang -- Career capital development of self-initiated expatriates in China / Ying Guo, Hussain Rammal, Peter Dowling -- Multiple aspects of readjustment experienced by international repatriates in multinational enterprises: a perspective of 'changes occurring over time' and 'changes due to cultural differences' / Yoko Naito -- Why expatriate compensation will change how we think about global talent management / Yvonne McNulty -- Global talent management and corporate entrepreneurship strategy / Vanessa Ratten, Joao Ferreira -- The effects of work values and organisational commitment on localisation of human resources / Justin Williams, Ramudu Bhanugopan -- Talent management & staffing in Central and Eastern Europe - an analysis of Bulgaria, Czech Republic, Hungary, Poland, Romania & Slovakia / Zoltan Buzady.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- International -- General; International business; International business enterprises -- Personnel management; International business enterprises -- Employees